High spin-wave propagation length consistent with low damping in a metallic ferromagnet - Flacke, Luis; Liensberger, Lukas; Althammer, Matthias; Huebl, Hans; Gepraegs, Stephan; Schultheiss, Katrin; Buzdakov, Aleksandr; Hula, Tobias; Schultheiss, Helmut; Edwards, Eric R. J.; Nembach, Hans T.; Shaw, Justin M.; et al. (Applied Physics Letters, 2019)
We report ultralow intrinsic magnetic damping in Co25Fe75 heterostructures, reaching the low 10-4 regime at room temperature. By using a broadband ferromagnetic resonance technique in out-of-plane geometry, we extracted the dynamic magnetic properties of several Co25Fe75-based heterostructures with varying ferromagnetic layer thicknesses. By measuring radiative damping and spin pumping effects, we found the intrinsic damping of a 26 nm thick sample to be α 0 3.18 × 10 - 4. Furthermore, using Brillouin light scattering microscopy, we measured spin-wave propagation lengths of up to (21 ± 1) μm in a 26 nm thick Co25Fe75 heterostructure at room temperature, which is in excellent agreement with the measured damping.
CRIS-Team Scopus Importer:2023-03-27